Impact of T‐cell depletion strategies on outcomes following hematopoietic stem cell transplantation for idiopathic aplastic anemia: A study on behalf of the European blood and marrow transplant severe aplastic anemia working party. Issue 1 (25th November 2018) - Samarasinghe, Sujith; Clesham, Katherine; Iacobelli, Simona; Sbianchi, Giulia; Knol, Cora; Hamladji, Rose‐Marie; Socié, Gerard; Aljurf, Mahmoud; Koh, Mickey; Sengeloev, Henrik; Dalle, Jean‐Hugues; Robinson, Stephen; et al.
Abstract: We retrospectively analyzed the outcomes of 1837 adults and children with severe aplastic anemia (SAA) who underwent matched sibling donor (MSD) and matched unrelated donor (MUD) hemopoietic stem cell transplantation (HSCT) between 2000 and 2013. Patients were grouped by transplant conditioning containing either anti‐thymocyte globulin (ATG) ( n = 1283), alemtuzumab ( n = 261), or no serotherapy (NS) ( n = 293). The risks of chronic GvHD were significantly reduced when ATG or alemtuzumab were compared with NS ( P = .021 and .003, respectively). Acute GVHD was significantly reduced in favor of alemtuzumab compared with ATG ( P = .012) and NS ( P < .001). By multivariate analysis, when compared with ATG, alemtuzumab was associated with a lower risk of developing acute (OR 0.262; 95% CI 0.14‐0.47; P < .001) and chronic GVHD (HR 0.58; 95% CI 0.35‐0.94; P = .027). OS was significantly better in ATG and alemtuzumab patients compared with NS ( P = .010 and .025). Our data shows inclusion of serotherapy in MSD and MUD HSCT for patients with SAA reduces chronic GVHD and provides a survival advantage over patients not receiving serotherapy. Notably, alemtuzumab reduced the risk of acute and chronic GvHD compared with ATG and indicates that alemtuzumab might be the serotherapy of choice for MSD and MUD transplants for SAA.